HISTORICAL ESSENTIALS OF INDIAN DRAMA IN ENGLISH (International Journal of Food and Nutritional Sciences, 2019)
The history of Indian English drama is rich and diverse, reflecting the cultural, social, andpolitical changes that have taken place in the Indian subcontinent over the years. Indian Englishdrama has evolved through various phases, from its inception during the British colonial periodto its vibrant contemporary forms.